Translation Procedures English-Indonesian in “The Sun and Her Flowers” Poems by Rupi Kaur - Firas Fauziah; Meita Lukitawati Sujatna (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims at what types of translation procedures are used in translating the poems of The Sun and Her Flowers, and what makes the translation procedures are applied by the translator in translating the poems of the Sun and Her Flowers. A poem is known as an outstanding literary work because it must convey the poet’s feelings and emotions in a theatrical way and imaginative style. Translating a poem is a crusade for every translator because of its content as literacy works. The poetic discourse has its unique from the common ones; it is form and content which must be independent. The data of this study were taken from The Sun and Her Flowers poem collection entitled ‘the underrated heartache’ written by Rupi Kaur and translated by Ni Made Purnamasari. The theoretical basis of this study is Newmark's (1988:81) translation procedures theory. The results of this study shown that are seven translation procedures, specifically shift or transposition (28,57%) is the most applied because of the differences in the languages system on the SL and TL, followed by modulation (23,81%), synonymy (14,29%), reduction (14,29%), equivalence (9,52%), naturalization (4,79%), and transference (4,79%).